(3YjhH GdfaS heOGhJgGs - (3eMeO Hf GdMSjf Hf eMeO GdSdej , GdfjSCHhQj CHh YHO GdQMef,J (B412 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi HYV GcQege Gddg eQVGJg Cf CNQL dge aUhdkG s
(3BNQgG (B:s
(3ajSbW HPdc YfgG YjHkG ef YjhHgG hGddg JYGdi jhabfG deJGHYI GdQShd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B58s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1183s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs